Development of Protective Clothing against Nanoparticle Based on Electrospun Nanofibers. (4th June 2012) - Faccini, M.; Vaquero, C.; Amantia, D.
Abstract : In this paper, the development of efficient protective clothing against nanoparticulate aerosols is presented. Nanofibrous mats of polyamide 6 (PA6) were deposited onto a nonwoven viscose substrate by electrospinning technique. The influence of electrospinning parameters, including solution concentration, viscosity, and conductivity, was studied for the production of nonwovens with controlled fiber diameter showing a size distribution ranging from 66 to 195 nm. By varying several process parameters, textiles with different thickness of the nanofiber layer and thus air permeability were obtained. A hot-press lamination process using a thermoplastic resin as glue was applied to improve the adhesion of the nanofiber layer onto the textile support. After 1500 cycles of repeated compression and torsion, the nanofiber layer was still firmly attached to the support, while mechanical damage is visible in some areas. The penetration of NaCl particles with diameter ranging from 15 to 300 nm through the electrospun textiles was found to be strongly dependent on nanofiber layer thickness. A really thin nanofiber coating provides up to 80% retention of 20 nm size particles and over 50% retention of 200 nm size nanoparticles. Increasing the thickness of the nanofiber mat, the filtration efficiency was increased to over 99% along the whole nanoparticle range. The results obtained highlight the potential of nanofibers in the development of efficient personal protective equipments against nanoparticles.